The Underexamined Role of Money and How it Undermines Nozick’s Case for Right Libertarianism - Grela, Helen (Ruch Filozoficzny, 2023)
In Anarchy, State and Utopia, Nozick presented his doctrine of right libertarianism, largely a contemporary restatement of Locke’s moral imperative that an individual’s rights to his life, liberty, and property are absolute and place limits on state action. Parallelly, Nozick espoused the free-market system as a framework that not only respects individual rights but ensures material benefits. While the free market results in radical inequalities in holdings and widespread dispossession, Nozick treats the process as morally just, and any state redistribution through taxation as wrong. However, neither Nozick nor his many critics fully considered the role of money in capitalist free markets, an omission I begin to address. Nozick asserts that money emerges pre-politically through the uncoerced actions of individuals, and that it derives its value from the commodity that underpins it. This conception of money underpins Nozick’s claims that a minimal state can be just and that the free-market system is a moral, efficient, and neutral allocator of resources. However, Nozick’s approach omits addressing how money’s general acceptability and stability are achieved. Answers can be found in heterodox economic paradigms, which put the state at the center of money creation, rendering money (and the state) incompatible with natural rights. Even if these issues were resolved, by insisting on money’s commodity nature, Nozick ignores the seventeenth century revolution in money, necessitated by the emergence of free-market capitalism and commodity money’s inability to underpin it. In other words, it is not commodity money but credit money that should be the proper object of Nozick’s analysis. I go on to analyze what credit money is, how it arose, and why some form of it is necessary in a free-market context. Ultimately, I argue that it is not compatible with natural rights and is itself redistributive.